A computational model for residual life assessment of dents generated by explosive loads in pipelines (2003)
The present work develops a finite elements computational model that describes the process of dynamic deformation in pipelines under explosive loads. The mechanical response of the material is modeled by means of an elastoviscoplastic constitutive law based on the Johnson-Cook equation. The model allows understanding the process of generation of dents through the dynamics phenomena and of the development and distribution of stress and strain. The model also allows studying the distribution and magnitude of residual stress allowing identifying critical areas in the dent. It is validated by means of the correlation of main variables with data obtained in experiments of generation of dents under controlled conditions. The model predicts the experimental results in a high grade allowing corroborating hypothesis of failure and residual life proposals for the pipe impacted.